2017
DOI: 10.19080/artoaj.2017.12.555852
|View full text |Cite
|
Sign up to set email alerts
|

The Exploration of Alpha Cellulose in Kapok Fruit as Raw Material for Rocket Propellant Production

Abstract: Rocket propellant is an essential part of weapons systems whose raw materials are largely composed of alpha-cellulose. These chemical compounds can be obtained in a variety of plants and animals, including kapok plants. The objective of this study was to explore the alpha cellulose derived from kapok fruit with a purity level above 90% and meets the qualification as a rocket propellant. Extraction, digestion, and purification were performed to know the presence of alpha cellulose and its quantity. Type Expert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Kapok nitrocellulose has low nitrogen content maybe due to its cellulose purities. Plant-based cellulose become suitable source for propellant ingredients when it has more than 90% purity [4]. Surface Morphological analysis.…”
Section: Solid State Science and Technology VIImentioning
confidence: 99%
See 1 more Smart Citation
“…Kapok nitrocellulose has low nitrogen content maybe due to its cellulose purities. Plant-based cellulose become suitable source for propellant ingredients when it has more than 90% purity [4]. Surface Morphological analysis.…”
Section: Solid State Science and Technology VIImentioning
confidence: 99%
“…According to Astika et. al., kapok cellulose can be converted to nitrocellulose for propellant application as long as cellulose purities are more than 90% [4]. The challenge of cellulose sourcering from plant is that it does not exist in pure form.…”
Section: Introductionmentioning
confidence: 99%
“…However, using kapok cortex fiber leaves waste that is not used. Astika et al (2017) previously reported that the peel of kapok contains š›¼-cellulose was > 90%. The content of š›¼-cellulose is relatively high in the kapok rind, indicating its potential as a source of microcrystalline cellulose material.…”
Section: Introductionmentioning
confidence: 97%